Mediating roles of perceived social support and hopelessness in the relationship between negative life events and self-identity acquisition among Chinese college students with left-behind and/or migrant experiences - Liu, Lijuan; Li, Jingbo; Li, Yanlan (Frontiers in Psychology, 2025)
IntroductionAlthough research examining the status of self-identity of college students has been conducted, few studies have explored the intrinsic mechanisms underlying the formation of self-identity acquisition (SIA) among college students with experiences of being left behind and/or migrant. The acquisition of self-identity is a crucial task during the college years, becoming even more significant in the aftermath of stressful life events.MethodsThis study employed Self-identity Acquisition (SIA), College Students Self-Rating Life Events Checklist, Perceived Social Support Scale (PSSS), Hopelessness scale to explore the impact of negative life events on the acquisition of self-identity among college students with left-behind and/or migrant experiences. A total of 1,240 college students were surveyed, comprising 180 with both left behind and migrant experiences (Group 1), 556 with only left-behind experiences (Group 2), 117 with migrant experiences (Group 3), and 387 with no left-behind or migrant experiences (Group 4).ResultsStudents in Group 1 exhibited the lowest levels of SIA, followed by those in Group 2, while participants in Group 4 demonstrated superior outcomes. The results of the correlation analysis showed that four variables were significantly correlated exclusively within the two groups of students experiencing left behind (Group 1 and Group 2), meeting the conditions for conducting a mediation test. In Group 2, perceived social support (PSSS) and hopelessness played separate mediating roles between negative life events and SIA. However, for individuals who experienced both left behind and migrant situations, there was no significant mediating effect of PSSS between negative life events and SIA; instead, hopelessness served as a stronger mediator compared to its role within the left-behind group. The two groups characterized by left-behind experiences, PSSS and hopelessness play chain mediating roles.DiscussionThese findings suggest that such dual experiences may lead to an increased perception of available support while simultaneously fostering despair that hinders the development toward acquiring a solid sense of identity. When individuals with left-behind experiences encounter feelings associated with despair following adverse life events, they tend to diminish their utilization of available supportive resources, which is not conducive to making positive and firm self-identity exploration and commitment.